Explaining COVID-19 postvaccination-related immune thrombotic thrombocytopenia: a hypothesis-generating in-silico approach. Issue 5 (30th November 2022) - Konstantinou, George N.
ABSTRACT: Cases that experienced COVID-19 postvaccination-related thrombosis have been reported after the first dose of ChAdOx1 nCov-19 (Vaxzevria, AstraZeneca) or Ad26.COV2.S (Johnson & Johnson/Janssen) vaccine. These rare thrombotic events were observed within the expected vaccine-induced seroconversion period and could be attributed to platelet-activating (auto)antibodies against platelet factor 4 (PF4). Newly, vaccine-induced, cross-reactive anti-PF4 antibodies could explain this observation. An in-silico analysis using the Basic Local Alignment Search Tool was used to identify sequence similarity between PF4 and antigens contained in or encoded by ChAdOx1 nCov-19 or Ad26.COV2.S vaccines. Only one sequence within the signaling peptide of the SARS-CoV-2 spike protein exhibited a high percent identity (85.71%) with PF4. This sequence overlaps with a proven immunogenic peptide recognized from convalescent COVID-19 sera and could be responsible for the formation of platelet-activating immunocomplexes in susceptible patients. Manipulation of the immunogenicity of this particular sequence within the encoded SARS-CoV-2 spike protein signaling peptide may eliminate this iatrogenic severe adverse effect.